2022
DOI: 10.1177/09544089221131147
|View full text |Cite
|
Sign up to set email alerts
|

Thermal scrutinization of magetohydrodynamics CuO engine oil nanofluid flow across a horizontal surface via Koo–Kleinstreuer–Li modeling: A thermal case study

Abstract: The current investigation aims to investigate the effects of ohmic heating, heat source, and adhesive dispersion in third-grade nanofluid flowing magnetohydrodynamics (MHD) boundary layer heat transmission using the Koo–Kleinstreuer–Li (KKL) model. As a basic fluid, copper oxide nano molecules are suspended in engine oil. The controlling formulas that regulate the fields of flow and heat conduction are partial differential equations (PDEs) which are then converted into models of nonlinear ordinary differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Meanwhile, Rana et al [ 22 ] showed the KKL model could be solved numerically using Homotopy Analysis Method (HAM) and Runge-Kutta-Fehlberg (RKF) method. Several studies examined the thermal properties of nanofluids on various surfaces using this concept [ [23] , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Rana et al [ 22 ] showed the KKL model could be solved numerically using Homotopy Analysis Method (HAM) and Runge-Kutta-Fehlberg (RKF) method. Several studies examined the thermal properties of nanofluids on various surfaces using this concept [ [23] , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%